THE ROLE OF DIASPORA IN PEACEBUILDING: THE CASE OF NIGERIA - Nneka Sophie Amalu; Ekong Demson; Yisrael Ini-Obong Jack-Rabin (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
The role of diaspora for a long time now has been seen from a negative perspective. They are usually seen as sponsors of conflict and terrorist activities in their homeland. However, there is a growing recognition that sees diaspora groups in a more positive light, that is playing a vital role in national development, integration, and peacebuilding. The paper aims to examine the role of the Nigerian diaspora in peacebuilding processes in Nigeria. Basing itself within the theoretical framework of transnationalism, the paper finds that they play certain roles of lobbying and advocacy, network and partnership, discussion and awareness, conflict mediation and negotiation, remittances, investment, and social development. However, playing these roles have become very daunting due to challenges such as lack of adequate fund, poor communication, lack of voting rights, fragmentation inter alia. The paper concludes that diaspora can contribute effectively to the peacebuilding of the nation so long as they maintain constant contact with their home country and recommended that peacebuilding of any nation is a national responsibility for all its citizens, home and abroad.  The government must create a safe, peaceful, and conducive environment for an effective and diaspora involvement in all peacebuilding processes of the nation.